Blacklight [videorecording (DVD)] - Neeson, Liam; Raver-Lampman, Emmy; Smith, Taylor John, 1995-; Stone, Yael; Boom, Claire van der; Quinn, Aidan (Universal, 2022)
Travis Block is a government operative coming to terms with his shadowy past. When he discovers a plot targeting U.S. citizens, Block finds himself in the crosshairs of the FBI director he once helped protect.